PELAKSANAAN PROGRAM ASISTENSI MENGAJAR ANGKATAN I DI SMK KEHUTANAN WANA WISATA SEKAROH LOMBOK TIMUR - Halimah, Baiq Elok Salsabila; Firmansyah, Harits; Hidayati, Maulia; Irham, Muhammad; Istiani, Ratna Ayu; Lestari, Dini; Prasetyo, Andrie Ridzki; Shabrina, Hasyyati; Fahrussiam, Fauzan; Chaerani, Nurul; Musdi, Musdi (Devote: Jurnal Pengabdian Masyarakat Global, 2024)
Education is the process to form an individual’s character into someone possesses useful knowledge in daily life. Teaching assistance Program was one of government’s efforts to improve the quality of learning activities in Indonesi. This article aims to provide an explanation of the implementation of Teaching Assistance Program for the first-year student of Forestry Program at Matarma Universita, which conducted at the Forestry Vocational School, Wana Wisata Sekaroh, Jerowaru Subdistrict, East Lombok. This activity took place approximately 4 months. The method of implementing the program cosnsisted of orientation, deployment, observation, planning program, report, program execution,and evaluation. The activities carried out included teaching program, assisting with school administrarion, creating a school garden, assisting with technology adaptatiom, conducting outreach to student about the graduate from Yunior high school and the nearest junior high school, creating banners and poster, establishing a Numeracy Literacy Garden, Planting tree sapling within the School, and making charcoal briquettes from corn husk, The series of activitie were carried out successfully.